THYROID FUNCTION TEST IN SICKLE-CELL DISEASE - SWAIN, JINGYASA; MOHANTY, BISWAJIT; patel, Nayan kumar; majhi, chakradhar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This cross-sectional study aimed to evaluate the thyroid function (triiodothyronine [T3], thyroxine [T4], and thyroid-stimulating hormone [TSH] levels) in patients with sickle-cell disease (SCD). Methods: This cross-sectional observational study was conducted in the general medicine department of the Veer Surendra Sai Medical College and Hospital, Burla, Sambalpur, Odisha (India). The investigation was performed in the sickle cell clinic, medical ward, and outpatient department of the institute. This study was conducted from November 2019 to October 2021. Sixty-eight patients with SCD were enrolled for assessing their thyroid function. The reference ranges for serum T4 (4.5–12 μg/dL), serum T3 (60–200 ng/dL), and TSH (0.3–5.5 uIU/mL) were defined to evaluate the thyroid function. Results: The average TSH, mean T4 level, and mean T3 level among the patients were 4.02, 4.67, and 74.15, respectively. The incidence rates of hypothyroidism and euthyroid status were 23.5% and 76.5%, respectively. While 9.59 g/dL was the mean hemoglobin level, 11–16 g/dL was observed in 42.6% of patients compared to <11 g/dL in 57.4% of patients. Patients within the age group of 14-25 years had a higher incidence of hypothyroidism (62.5%). The differences in hypothyroidism between males and females were statistically insignificant (68.8% vs. 31.2%, p = 0.11). Conclusion: Patients with SCD had clinically significant reductions in T3 and T4 levels. In addition, higher levels of TSH and reductions in endogenous T3/T4 levels were observed in male patients. Overall, SCD was associated with a higher incidence of hypothyroidism.